PROCESS FOR DRINKING FROM NUTRACEUTICAL MYRCIARIA DUBIA (CAMU CAMU), AIMED TO REDUCE EFFECT GENOTOXICITY IN SCHOOL-AGE CHILDREN - Salas de la T., N. (2009)
We propose a process for making a nutraceutical beverage, from camu camu, which strengthens the immune system through their high levels of vitamins, essential amino acids and minerals. This process involves the primary treatment unit operations such as selection, sorting, bleaching, pulping, pulp refining and pulp pasteurization of camu camu. It has managed to drink, preserving all its nutritional properties. The report analyzes the drinking 1334 mg ascorbic acid / 100 ml and 197.90 ppm levels of calcium: magnesium 47.27 ppm to 1.24 ppm of Zn and energy 66.38 calories per 100 ml.